Evidence for Steroid Control of the Metabolism of Profibrinolysin - Pilgeram, L. O; Amundson, B. A; Lofgren, P. E (Thrombosis and Haemostasis, 1964)
Daily therapy with 5 mg of norethynodrel and 0.075 mg of ethynylestra- diol-3-methyl ether (Enovid) is associated with a 34.7% (P < 0.001) increase in the activity of human serum profibrinolysin (plasminogen).